Estrutura tarifária e custos no setor de saneamento : uma abordagem a partir da gestão da água e desempenho - Correia, Thamirys de Sousa (2024)
This research aimed to discuss the tariff structure and water management with the support of a multi-methodological approach (STUDY 01) and verify the relationship between costs and tariff structure in performance measures in the sanitation sector (STUDY 02). We sought to achieve this objective through two studies, based on Systems Thinking (STUDY 01) and Water Regulation (STUDY 01 and STUDY 02). To this end, each study used a different methodology. In STUDY 01, based on Strategic Options Development and Analysis (SODA), in which through online meetings (2019-2023) and correspondence survey (2020) with experts (Strategic and Commercial Management, Controllership Management, Environmental Management, Chemical and Engineers), a cognitive map was developed. Continuing, with System Dynamics (SD) a model was proposed for the Gramame Hydrographic Basin. For SD, data were extracted from AESA, SINS and meetings with experts. The simulation period was from 2013 to 2022. The main findings are that through the simulations for tariff adjustments, when applying an increment rate, so that additional revenue can be obtained, the calculations carried out sought to optimize tariffs, with alternative tariff structures, to meet the objective of cost recovery (production and distribution, investments and environmental costs). When considering the tariff adjustments in the simulations carried out in the last year (R$4.88, R$5.01, R$5.14, respectively), in relation to the average tariff charged (R$4.85) in the same year (2022), the model can be used to discuss better strategies for defining a tariff structure, in a way that takes water conservation into account. To this end, it is suggested that tariff adjustments should be made for the largest consumers in the residential category. Likewise, through simulations to control losses, it is clear how much this parameter is intrinsically linked to water management and this is due to better water conservation by increasing the volume in the water balance. This result could be confirmed by the Monte Carlo sensitivity test. In STUDY 02, with a sample of 1,526 Brazilian municipalities and data extracted from the SNIS, whose explanatory variables refer to quality and operational performance, the dependent variables selected are costs with exploration services, measured by chemical products and the supply tariff of water, measured by the average tariff. This for a period that comprised 1999-2020. Quantile regression models were used. The main results indicate that the number of complaints from customers are related to costs with exploration services. A possible justification is that some of the complaints may be related to water quality. Furthermore, the number of complaints from customers, the number of turbine samples, the urban water service index and the distribution loss index are positively related (in some of the analyzed quartiles - 25th quantile, 50th quantile and 75) with water supply tariff. It is noteworthy that there is a negative relationship between the quantity of samples for residual chlorine and the water supply tariff, in the largest quartiles, with a possible explanation being the fact that the greater the sampling in laboratories for analysis, the greater the verification of whether the quantity of residual chlorine is arriving adequately at all points in the system, avoiding excess costs and not passing this cost on to the end consumer. In view of the results presented, the two empirical studies bring contributions to the literature and practical implications, considering the initiative to address tariffs, costs, water management and performance as critical components of public policies.